The effect of chiropractic care on jet lag of finnish junior elite athletes - Straub, W. F.; Spino, M. P.; Alattar, M. M.; Pfleger, B.; Downes, J. W.; Belizaire, M. A.; Heinonen, O. J.; Vasankari, T. (Journal of Manipulative and Physiological Therapeutics, 2001)
OBJECTIVE: To determine the effect of chiropractic care on jet lag in Finnish junior elite athletes. SUBJECTS: Fifteen Finnish junior elite athletes. METHODS: Through use of a table of random numbers, each athlete was assigned by sex to one of 3 groups: chiropractic adjustment, sham adjustment, or control. As needed, the chiropractic adjustment group athletes (n = 5) were adjusted on a daily basis by licensed chiropractors using a toggle/recoil procedure. The sham adjustment group athletes (n = 5) received sham adjustments on a daily basis by licensed chiropractors. The control group athletes (n = 5) were not adjusted or sham-adjusted but participated in all test protocols. Sleep, jet lag, chiropractic, and mood data (the last acquired through use of the Profile of Mood States) were collected on a daily basis for 18 consecutive days. RESULTS: Repeated-measures analyses of variance (3 x 2) of total mood disturbance scores and heart rate variables indicated that there were no significant (.05 level) between-group differences. Sleep data were analyzed through use of a 3 x 2, repeated-measures multivariate analysis of variance. Pillai's trace indicated that there were no between-group differences. Self-assessment of jet lag by participants after traveling to Georgia and after returning to Finland showed no between-group differences. CONCLUSIONS: It was concluded that chiropractic care did not reduce the effects of jet lag.